A rare presentation of stroke in young age ( moyamoya disease) - Amal F Radwan; Afaf Hemaida; Ahmed Naguib (SpringerOpen, 2013)
A 37-year-old hypertensive housewife presented with a sudden onset of left-sided hemiplegia, hemianaesthesia, dysarthria and urinary incontinence. The condition was preceded by recurrent attacks of motor neurological deficits over a 3-year duration. She reported a history of a fall from a height at the age of 10, which was followed by a hearing deficit and a history of two caesarean sections after eclampsia. The blood pressure was 170/100 mmHg. Laboratory investigations revealed hyperglycaemia (fasting glucose 306 mg/dl) and normal kidney function tests. The computed tomography scans revealed old multiple bilateral cerebral infarcts with recent intracranial haemorrhage in the right parietal region. The inflammatory markers (ESR and CRP) and immune profile (ANA, anti-ds DNA and ANCA) were found to be normal. Cerebral angiography revealed a complete occlusion of the intracranial parts of both internal carotid arteries at their supraclinoid segments along with the proximal parts of the anterior cerebral artery and middle cerebral artery, with collaterals from the posterior circulation. Consequently, the diagnosis of moyamoya disease with the collaterals was confirmed. Antihypertensive medications and insulin were administered. Cerebral dehydration measures were undertaken with partial improvement. A superficial temporal artery-middle cerebral artery bypass operation was performed with some postoperative improvement. One month later, she suffered a new stroke with severe impairment of the level of consciousness; the computed tomography scans revealed a large recent cerebral infarct, her condition deteriorated rapidly and she died shortly thereafter.